2021
DOI: 10.3389/fncel.2021.741292
|View full text |Cite
|
Sign up to set email alerts
|

Neural Burst Firing and Its Roles in Mental and Neurological Disorders

Abstract: Neural firing patterns are critical for specific information coding and transmission, and abnormal firing is implicated in a series of neural pathologies. Recent studies have indicated that enhanced burst firing mediated by T-type voltage-gated calcium channels (T-VGCCs) in specific neuronal subtypes is involved in several mental or neurological disorders such as depression and epilepsy, while suppression of T-VGCCs relieve related symptoms. Burst firing consists of groups of relatively high-frequency spikes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 106 publications
0
10
0
Order By: Relevance
“…Stereotaxic local delivery of ssw-CNTs at the affected regions could be used to ameliorate the condition by reducing the bursting activity to normal non-pathological levels to restore motor dysfunction. Depression is another mental condition of mood disorder, associated with increased bursting in the lateral habenula (Shao et al, 2021) where ssw-CNT could be used. A miniaturized neural drug delivery system recently developed (Dagdeviren et al, 2018), could be used for localized delivery of the ssw-CNTs in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotaxic local delivery of ssw-CNTs at the affected regions could be used to ameliorate the condition by reducing the bursting activity to normal non-pathological levels to restore motor dysfunction. Depression is another mental condition of mood disorder, associated with increased bursting in the lateral habenula (Shao et al, 2021) where ssw-CNT could be used. A miniaturized neural drug delivery system recently developed (Dagdeviren et al, 2018), could be used for localized delivery of the ssw-CNTs in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The increased STC in DBP treated embryos having physiological neural circuits indicating that DBP does not have any effect on the neuronal growth but it induces firing rate of developing neurons but not on mature locomotive behavior, which is regulated by the hindbrain and spinal circuits together. Studies showed abnormal firing is implicated in several neurological or mental disorders, including depression and epilepsy (Shao et al, 2021). Thus, embryos exposed to DBP may develop neurological disorders in adult stage without any visible morphological defects.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that burst firing elevates extracellular dopamine concentration in an exponential manner (Gonon, 1988 ; Floresco et al, 2003 ). Burst firing can be found in various brain regions; however, its functions vary in different regions and cell types (Shao et al, 2021 ). It was recently reported that the burst firing of lateral habenula neurons was increased in depression animal model (Yang et al, 2018 ), whereas enhancing burst firing and 5-HT releasing were critical for the regulation of depression and anxiety states in DRN (Hornung, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that the burst firing of lateral habenula neurons was increased in depression animal model (Yang et al, 2018 ), whereas enhancing burst firing and 5-HT releasing were critical for the regulation of depression and anxiety states in DRN (Hornung, 2003 ). Although the ionic mechanism of burst firing is different in neuronal subtypes and brain regions (Shao et al, 2021 ), blockade small-conductance Ca 2+ -activated potassium (SK) channels will promote the bursting firing of 5-HT neurons (Rouchet et al, 2008 ). In future studies, SK blocker UCL 1,684 should be used to explore its effects on putative survival unit activities.…”
Section: Discussionmentioning
confidence: 99%